L'Empire des signes - Barthes, Roland 1915-1980 (Geneva Skira, 1970)
The 'Empire of Signs' was presented as an introduction to Japanese culture when it was published in 1970. It narrates his observations and the omnipresence of signs in Japanese daily life. 'L'Empire des signes' also contextualizes France's international relations with Japan, after a colonial period. With this book, Barthes offers a broad-ranging meditation on the culture, society, art, literature, language, and iconography of Japan.
Keywords: Travel; Cuckoo; Japan